Local Government Efforts in Protecting Productive Wetland Forests as the Basis for Food Security in South Kalimantan - Yulia Audina Sukmawan; Ifrani Ifrani; Muhammad Topan; Daddy Fahmanadie; M. Ali Amrin; Dwi Damayanti; Saraya Aisya Awanis (International Journal of Law, Environment, and Natural Resources, 2025)
The environment as a legal subject is fundamentally regulated by law. Efforts to protect and manage the environment in Indonesia continue to experience developments in its regulations, especially with the enactment of Law No. 32 of 2009 concerning Environmental Protection and Management, which replaced Law No. 23 of 1997 concerning the Environment. In addition to Law No. 32 of 2009, which serves as the parent law in the environmental sector, there are also other sectoral laws related to the environment, such as laws in the fields of forestry, mining, natural resources, and others. Peat swamp forests are one of the types of wetlands that are most threatened in Indonesia due to pressure from various human activities. Forest conversion or forest conversion into agricultural land, plantations, and production forests can threaten the existence of natural peat swamp forests. The purpose of this study is to determine and analyze the role of local governments in protecting wetland production forests in supporting food security in South Kalimantan and analyze converted agricultural land. Based on the research results obtained, 1,300 hectares of agricultural land have become yellow due to the increasingly rampant land conversion. Farmer groups in South Kalimantan are still active as farmers, 75% of whom are sharecroppers. By using annual crops, farmers in South Kalimantan produce 10-11 tons of rice per year with a 6-month planting period. However, unfortunately, the government program that encourages farmers to achieve an agricultural index of 200 per year has not been fully achieved, South Kalimantan's agricultural index is still at 100, considering that natural conditions have a major influence on the success of planted rice. Through this research, all problems regarding wetland production forests will be solved in supporting food security in South Kalimantan.